A dominant role of transcriptional regulation during the evolution of C4 photosynthesis in Flaveria species - Ming-Ju Amy Lyu; Huilong Du; Hongyan Yao; Zhiguo Zhang; Genyun Chen; Yuhui Huang; Xiaoxiang Ni; Faming Chen; Yong-Yao Zhao; Qiming Tang; Fenfen Miao; Yanjie Wang; et al. (Nature Communications)
Abstract C4 photosynthesis exemplifies convergent evolution of complex traits. Herein, we construct chromosome-scale genome assemblies and perform multi-omics analysis for five Flaveria species, which represent evolutionary stages from C3 to C4 photosynthesis. Chromosome-scale genome sequence analyses reveal a gradual increase in genome size during the evolution of C4 photosynthesis attributed to the expansion of transposable elements. Systematic annotation of genes encoding C4 enzymes and transporters identify additional copies of three C4 enzyme genes through retrotranspositions in C4 species. C4 genes exhibit elevated mRNA and protein abundances, reduced protein-to-RNA ratios, and comparable translation efficiencies in C4 species, highlighting a critical role of transcriptional regulation in C4 evolution. Furthermore, we observe an increased abundance of ethylene response factor (ERF) transcription factors and cognate cis-regulatory elements associated with C4 genes regulation. Altogether, our study provides valuable genomic resources for the Flaveria genus and sheds lights on evolutionary and regulatory mechanisms underlying C4 photosynthesis.